PERAN ORANG TUA DALAM MENINGKATKAN STATUS GIZI ANAK PAUD MELALUI EDUKASI GIZI DI TKN HANDAYANI SUMBER - Annisa Rahma Azzahra; M. Arif Syarif Hidayatullah; Rina Hizriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Nutritional status problems in early childhood remain a serious concern in Indonesia, including in Early Childhood Education (PAUD) settings. Parents play a crucial role as the primary educators in shaping children's eating habits and nutritional patterns from an early age. This study aims to determine the nutritional status of early childhood students at TKN Handayani Sumber, analyze the implementation of nutritional education for parents, and describe the role of parents in applying healthy and nutritious eating patterns for children within the family environment. This research employed a qualitative approach using a descriptive method. The research participants were parents of students at TKN Handayani Sumber. Data were collected through in-depth interviews, observation, and documentation. Data validity was established through source triangulation and technique triangulation. The results indicate that the majority of children at TKN Handayani Sumber have normal nutritional status based on weight and height indicators. The implementation of nutritional education at the school has made a positive contribution to increasing parents' knowledge of balanced nutrition. Parents' roles in providing nutritious food, modeling healthy eating behaviors, and monitoring children's eating patterns have been shown to contribute positively to children's nutritional status. Nevertheless, several challenges were identified, including limited parental time and the inconsistent implementation of balanced nutrition principles at home. This study concludes that nutritional education supported by the active involvement of parents is an important factor in improving children's nutritional status and supporting the optimal growth and development of early childhood children.